Before, during and after the COVID-19 pandemic - Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2020)
The social disruption that had characterized the rapid progression of CoVid-19 infection in Italy in the first months of 2020 appeared again in the days in which this journal issue is being published. Due to what is defined as the second wave of the SARS-CoV-2 pandemic, measures to contain the contagion were still necessary, such as social distancing, isolation, the suspension of some production activities, closure of the majority of educational activities in presence in schools and universities. [...]